Effect of temperature on rice (Oryza sativa) seedling disease incidence and severity in Bangladesh - MD. TANBIR RUBAYET; FARHANA PRODHAN; MD. ABDULLAH AL MAMUN; MD. ABDUL KADER; MD. MOTAHER HOSSAIN; MD. MAHIDUL ISLAM MASUM; MUHAMMAD ZIAUL HOQUE; MD. MIZANUR RAHMAN; JATISH CHANDRA BISWAS (Nusantara Bioscience, 2025)
Abstract. Rubayet MT, Prodhan F, Mamun MAA, Kader MA, Hossain MM, Masum MMI, Hoque MZ, Rahman MM, Biswas JC. 2025. Effect of temperature on rice (Oryza sativa) seedling disease incidence and severity in Bangladesh. Nusantara Bioscience 17: 235-242. Seedling diseases are strongly influenced by temperature and cultivation environment, posing serious challenges to rice production under changing climates. To investigate these effects, two simultaneous experiments were conducted in Bangladesh, at Rangpur (25.6962°N, 89.2676°E) and Gazipur (24.0361°N, 90.3963°E) using BRRI dhan28 and BRRI dhan29 under open-field and polythene-covered conditions. Seedling emergence was consistently higher in polythene-covered plots, suggesting improved establishment in warmer microclimates. Three major diseases were detected across sites: bakanae (Fusarium moniliforme), blast (Pyricularia oryzae), and brown spot (Bipolaris oryzae). Varietal and environmental interactions were evident, with BRRI dhan29 showing greater susceptibility to bakanae in open-field conditions, while BRRI dhan28 was more prone to blast. Brown spot severity showed no significant differences between locations, indicating a lesser influence of variety and microclimate. Physiological observations revealed that healthy seedlings exhibited higher chlorophyll content (Soil Plant Analysis Development/SPAD values), whereas bakanae-infected seedlings displayed abnormal elongation relative to healthy plants. These results demonstrate that temperature and cultivation environment exert significant effects on rice seedling health, and that varietal responses differ according to disease type. Findings underscore the need for integrating varietal resistance and environment-specific management strategies to mitigate seedling disease risks in the context of climate change.